The library for parallel execution of rpC-programs under Win32 - V. V. Vasilchikov; Shubin (Моделирование и анализ информационных систем, 2008)
The new version of the library for parallel execution of rpC-programs under Win32 is reviewed. This library is a significant part of the RpmShell software for developing recursive parallel programming style.